Increased expression of pro‐inflammatory genes in abdominal subcutaneous fat in advanced chronic kidney disease patients - Witasp, A.; Carrero, J. J.; Heimbürger, O.; Lindholm, B.; Hammarqvist, F.; Stenvinkel, P.; Nordfors, L. (Journal of internal medicine, 2011)
.  Witasp A, Carrero JJ, Heimbürger O, Lindholm B, Hammarqvist F, Stenvinkel P, Nordfors L (Karolinska Institutet, Stockholm, Sweden). Increased expression of pro‐inflammatory genes in abdominal subcutaneous fat in advanced chronic kidney disease patients. J Intern Med 2011; 269: 410–419. Objectives.  Low‐grade systemic inflammation, oxidative stress and peripheral insulin resistance are intimately associated and contribute to the increased risk of cardiovascular complications in advanced chronic kidney disease (CKD). Because altered adipose tissue activities have previously been linked to pathophysiological processes in various inflammatory and metabolic diseases we hypothesized that the uraemic milieu in patients with CKD may interact with the adipose tissue, provoking an unfavourable shift in its transcriptional output. Design.  Twenty‐one adipokine mRNAs were quantified in abdominal subcutaneous adipose tissue (SAT) biopsies and serum/plasma concentrations of inflammatory markers and related protein products were measured. Setting.  The study was conducted at the Karolinska University Hospital, Huddinge, and Karolinska Institutet, Stockholm, Sweden. Subjects.  Thirty‐seven patients with CKD [15 women, median 58 (interquartile range 49–65) years] and nine nonuraemic individuals [four women, age 62 (45–64) years] were recruited prior to initiation of peritoneal dialysis catheter insertion or elective hernia repair/laparoscopic cholecystectomy, respectively. Results.  Even after correction for body mass index, SAT from patients showed a significant upregulation of inflammatory pathway genes interleukin 6 (3.0‐fold, P = 0.0002) and suppressor of cytokine signalling 3 (2.5‐fold, P = 0.01), as well as downregulation of leptin (2.0‐fold, P = 0.03) and the oxidative stress genes uncoupling protein 2 (1.5‐fold, P = 0.03) and cytochrome b‐245, alpha polypeptide (1.5‐fold, P = 0.005), in relation to controls. Conclusions.  These gene expression differences suggest that inflammatory and oxidative stress activities may be important features of the intrinsic properties of uraemic adipose tissue, which may have significant effects on the uraemic phenotype.